Depressive symptoms and cognitive and behavioral strategies among adolescents: Gender and age differences - Malinauskienė, Oksana; Žukauskienė, Rita (Psichologija, 2003)
Adolescence can be described as a transitional period between childhood and adulthood consisting of a variety of changes in role patterns, obligations, and normative expectations (Nurmi, Poole, Kalakoski, 1993). Whether or not adolescents effectively adapt to the new social roles is determined, in part, by cognitive and behavioral strategies they apply in social situations. Strategies have been defined as the latent mental structures that are stored and carried forward over time in memory and then activated by a specific goal or a situation (Crick & Dodge, 1994; Eronen, 2000). They could also be described in terms of two major processes, cognitive planning and the evaluation of behavioral outcomes by means of causal attributions (Nurmi, Onatsu, Haavisto, 1995; Onatsu-Arvilommi & Nurmi, 2000). The term "cognitive and behavioral strategy" is used to refer to the ways in which people typically feel and react in challenging achievement and affiliative situations by anticipating behavioral outcomes and related affects, and by planning and investing effort in the situation at hand. Another line of study is concerned with the attributional style as a developmentally acquired personality characteristic, which is examined in the relation with depression and other internalized problems. The cross-sectional association between attributional patterns and self-reported depression in youth is found across age groups, in both boys and girls, and in clinical (inpatient, outpatient) and non-clinical samples (Gladstone, & Kaslow, 1995; Joiner & Wagner, 1995). However, despite the abundance of data on the depression-attributional style link, there information about the age and gender differences is rather controversial. Consequently, the aims of this study were to investigate the age and gender differences in links between depressive symptoms, and cognitive and behavioral strategies.In this cross - sectional study, the links between depressive symptoms, cognitive and behavioral strategies, gender, and age were explored. Un-selected sample of adolescents (N = 418, from 16 to 18 years-of age) was given a test measuring their cognitive and behavioral strategies in achievement and in affiliative contexts, and test measuring emotional problems of adolescents. The YSR (Achenbach, 1991) has been used to assess depressive symptoms. Cronbach alpha reliability for YSR depression subscales was 0.829. The cognitive and behavioral strategies were assessed using Lithuanian version of the SAQ (Nurmi, et al., 1995), which consists of 60 statements, and ten subscales. Thirty items on this scale measure cognitive and behavioral strategies "in social context" (five subscales) and another thirty items scale measure cognitive and behavioral strategies in an "achievement context" (Success expectation subscale, Task-irrelevant behavior subscale, Avoidance subscale, Master orientation subscale, Pessimism subscale). The translation of these scales into Lithuanian language followed established guidelines. Cronbach alpha reliabilities for these subscales ranged from 0.55 to 0.69, showing acceptable internal consistency (Zukauskiene, Sondaite, 2003).First, depressive symptoms were found to be higher for girls than for boys. Our data is showing that the symptoms of depression tend to increase with age both for boys and for girls. Next, depressive symptoms were significantly predicted by 5 strategies for girls. Among these strategies, we have found 3 maladaptive strategies (pessimism, task irrelevant behavior in achievement context, and task irrelevant behavior in affiliative context) and 2 adaptive strategies (mastery-orientation in achievement context and success expectation in affiliative context). For boys, depressive symptoms were significantly predicted only by one maladaptive strategy (pessimism in social context). These differences between gender, and the lower percent of explained variance by regression analysis for boys than for girls, are discussed in the context of gender differences in etiology of depression.
Keywords: depressive symptoms; cognitive strategies; behavioral strategies; adolescents; gender; age